2010
DOI: 10.4037/ajcc2010624
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Face, Legs, Activity, Cry, Consolability Behavioral Tool in Assessing Acute Pain in Critically Ill Patients

Abstract: Background Few investigators have evaluated pain assessment tools in the critical care setting.Objective To evaluate the reliability and validity of the Face, Legs, Activity, Cry, Consolability (FLACC) Behavioral Scale in assessing pain in critically ill adults and children unable to self-report pain.Methods Three nurses simultaneously, but independently, observed and scored pain behaviors twice in 29 critically ill adults and 8 children: before administration of an analgesic or during a painful procedure, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
138
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(156 citation statements)
references
References 29 publications
(34 reference statements)
3
138
0
8
Order By: Relevance
“…Pain assessment methods such as self-reports, for example Faces scale [10]; behaviour observation, for example the FLACC scale (Facial expression, Legs, Activity, Cry and Consolability) scale [11] and caregiver reports may be used. Once identified, several measures are used to treat pain.…”
Section: Introductionmentioning
confidence: 99%
“…Pain assessment methods such as self-reports, for example Faces scale [10]; behaviour observation, for example the FLACC scale (Facial expression, Legs, Activity, Cry and Consolability) scale [11] and caregiver reports may be used. Once identified, several measures are used to treat pain.…”
Section: Introductionmentioning
confidence: 99%
“…14 Voepel-Lewis T et al validated the use of FLACC in intensive care units, with a good correlation with numeric 0-10 scales. 15 The scale was translated and validated for use in Portuguese language. 13 After the non-pharmacological measures have been adopted and the most adequate scale has evaluated the patients, we shall initiate the pharmacological treatment of pain.…”
Section: Resultsmentioning
confidence: 99%
“…4,9,10 Scales were developed and validated due to theses difficulties, and their use is now well established for the evaluation and intervention on pediatric pain. [9][10][11][12][13][14][15][16][17][18] The implementation of scales has already shown to be plausible and effective on intensive care units, both adult and pediatric. Mansouri P et al demonstrated a decrease of 3 days in ICU stay with the use of protocols and scales for analgesia and sedation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After extubation, patients were taken to recovery room; the postoperative pain was evaluated by FLACC Scale [13] for pain assessment in children (Face, Legs, Activity, Crying and Consolability), each given a score of 0-2 and the total score is from 0 to 10 at 0 h, 4 h, 8 h and 24 h postoperative. Also duration of analgesia and time to first spontaneous leg movement in both groups were monitored.…”
Section: Methodsmentioning
confidence: 99%